Leaving child without reasonable supervision in Malaysia: An overview under child (amendment) act 2016 and international legal framework / Irma Kamarudin...[et al.] - Kamarudin, Irma; Mohamad Sirat, Nur Irinah; Che Rose, Sarirah; Abu Bakar, Syatirah (Universiti Teknologi MARA, Kedah, 2016)
The focal point of this paper is on the right of the children who have been left without reasonable supervision by their parent or guardian. Even though we already have law to govern this issue, there are still numerous of cases occurred in Malaysia which has caused traumatizing consequences to the nation. It would be detrimental to the children in Malaysia if there is no attempt taken to figure out the solution. The prevalence of this issue in Malaysia has invite us to conduct a study on this matters from the perspective of Malaysian's legislation and other countries' rule and regulation.